Avaliação da ingestão de nutrientes, segundo padrão alimentar de idosos do município de Botucatu - SP - Nunes, Patrícia Moraes Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Objective: This study aims to analyze the nutrient intake for each eating patterns of older individuals users of the Primary Health Care Units of Botucatu - SP. Methodology: This is a cross-sectional study with 172 urban older individuals selected by stratified sampling among health care units in Botucatu. Data were collected from March to June 2011, through the application of a food frequency questionnaire, socioeconomic questionnaire and anthropometric measurements. We analyzed the means of daily nutrient intake, comparing gender through generalized linear model with gamma distribution adjusted by energy. Then mean comparisons were made of nutrient intake of individuals with high adherence to eating patterns (identified in a previous study), through analysis of variance (ANOVA), adjusted for energy and followed by comparison tests. The software Statistical Analysis System (SAS) performed the statistical treatments, and it was considered significance level of 5% (p<0.05). Results: The mean of retinol intake was higher in women. The means of iron, manganese and alcohol intake were higher in men. The eating pattern Healthy foods showed the highest mean of retinol in both gender; and it presented the highest mean of vitamin E in men, with a significant difference from all other eating patterns. A high adherence to Snacks and weekend meal had lower means of vitamin B12, vitamin C, phosphorus and retinol; and higher means of iron, manganese and magnesium. A high adherence to Fruits showed the lowest means of fiber intake for both gender, it did not differ only of the Soft diet eating pattern. Light and whole foods showed the highest means of vitamin C in women, with a significant difference from all other eating patterns. A high adherence to Soft diet had less protein and more added sugar, compared to the others eating patterns. A high adherence to Traditional diet showed higher means of nutrient intake when it was compared to ...

Objetivo: Analisar a ingestão de nutrientes, segundo padrão alimentar de idosos cadastrados na rede básica de saúde do município de Botucatu-SP. Metodologia: Estudo transversal, com 172 idosos da zona urbana, selecionados por amostragem estratificada entre as unidades básicas de saúde de Botucatu. Os dados foram coletados de março a junho de 2011, através da aplicação de um questionário de freqüência alimentar, questionário socioeconômico e avaliação antropométrica. Analisaram-se as médias de ingestão de nutrientes por dia, comparando os sexos, através de modelo linear generalizado com distribuição gama, ajustado por energia. Em seguida, foram feitas comparações de médias de ingestão de nutrientes dos indivíduos com alta adesão aos padrões alimentares (identificados em estudo anterior), através de Análise de Variância (ANOVA), ajustado por energia e seguido de testes de comparações. Utilizou-se o programa SAS e p <0,05 para os testes. Resultados: A média de consumo de retinol foi maior em mulheres e as médias de ferro, manganês e álcool foram mais elevadas em homens. O padrão Saudável se destacou por apresentar a maior média de retinol, em ambos os sexos; e a maior média de vitamina E no sexo masculino, com diferença significativa em relação a todos os demais padrões. A alta adesão ao padrão Lanches e refeição de final de semana apresentou médias menores de vitamina B12, vitamina C, fósforo e retinol; e médias mais elevadas de ferro, manganês e magnésio. A alta adesão ao padrão Frutas se destacou por apresentar a menor média de ingestão de fibras, para ambos os sexos, não diferindo apenas do padrão Dieta branda. O padrão Light e integral se destacou por possuir as médias mais elevadas de vitamina C no sexo feminino, com diferença significativa em relação a todos os demais padrões. A alta adesão ao padrão Dieta Branda apresentou menos...
Keywords: Idoso - Nutrição; Nutrientes; Saúde pública; Estudos transversais; Aged; Public health